2015
DOI: 10.1093/aobpla/plv084
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation and hybrid identification using microsatellite markers in closely related wild species

Abstract: Despite extensive morphological diversity and different floral syndromes, two wild Petunia species are closely related, present high genetic similarity, and field observations suggest natural hybridization between them. Here we described helpful tools for evolutionary studies addressing genetic population, interspecific hybridization, and plant speciation. Based on previously described microsatellites of Petunia hybrida we were able to identify private alleles characterizing species and their putative hybrids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 55 publications
1
48
0
Order By: Relevance
“…Each locus showed at least one private allele per population, which is in line with EST-SSR-based studies of Petunia species in Brazil [73] and Mangifera species in Australia [74].…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 85%
“…Each locus showed at least one private allele per population, which is in line with EST-SSR-based studies of Petunia species in Brazil [73] and Mangifera species in Australia [74].…”
Section: Genetic Diversity and Differentiationsupporting
confidence: 85%
“…Neighbour-joining tree of 126 individuals of petunia (coloured by taxon), constructed based on a matrix of microsatellite alleles shared among individuals (Turchetto et al 2015). Barik et al (2006) also found the genetic variation within the two species of Hibiscus and 16 varieties of Hibiscus rosa-sinensis L. through random amplified polymorphic (RAPD) markers.…”
Section: Figmentioning
confidence: 95%
“…Thirteen Microsatellites or SSR (simple sequence repeat markers) developed by Kimura et al (2009) in carnation by enriched genomic library method and its use for hybrid analysis. The parentage of two carnation mutant varieties obtained from intra-specific crosses and hybridity of the progenic Turchetto et al (2015) analysed two closely related species of Petunia exserta, which has a narrow endemic range and grows exclusively in rocky shelters, and Petunia axillaris, which was widely distributed and comprises three allopatric subspecies by EST-SSRs markers. Four major groups were identified in clustering analyses, which indicated that there are genetic distinctions among the groups (Fig.3).…”
Section: Figmentioning
confidence: 99%
“…Molecular markers involve amplification of specific amplified fragment length polymorphism (AFLP) [87], rapid amplification of polymorphic DNA (RAPD) [88] and single sequence repeat polymorphism (SSR) [89] markers related to fertility restoration and specific ribosomal DNA sequences. Molecular markers are the most reliable for identification of hybrids due to their unlimited number in the genome in comparison to chemical profiling which is time-consuming and limited in predicting hybrid ancestry [86].…”
Section: Selection Schemes For Sexual Hybridsmentioning
confidence: 99%